Developing the European Health Literacy Action Plan using a transformative future scenario planning approach. (30th September 2020) - Sørensen, K; Koylyu, A; Mikkelsen, B
Abstract: Background: The 53 Member States of the WHO European Region adopted in 2019 a health literacy roadmap and a resolution to develop an action plan to guide the work of the Member States. The development of the action plan builds on achievements regarding the EU funded European Health Literacy Survey and the WHO action networks on health literacy measurement and NCD related demonstration projects as well as the multiple national initiatives launched in the European region in the last decade. Methods: Scenario planning is a methodology that uses the inherent human capacity for imagining futures to better understand the present regarding the development of a new strategy or action plan. In the kick-off phase of the development process of the health literacy action plan, a transformative future scenario planning approach was applied in combination with a SWOT analysis (strengths, weaknesses, opportunities, threats) of current achievements, challenges and gaps considering the development of health literate societies involving 50 experts from a wide range of sectors and disciplines. Additionally, an iterative process followed including technical consultations with experts in Europe in preparation for a governmental consultation. Results: The SWOT analysis, long-sight planning and generation of complementary concrete actions served as basis for the development of the action plan highlighting its relevance, sustainability and accountability. Additionally, the health literacy plan was developed in a process of co-creation with the wider health literacy community as well as stakeholders with multiple backgrounds in research, policy, education and practice. Conclusions: The European health literacy action plan is multi-sectoral, people-centred and targeted governmental actions with the aim of developing health literate societies and populations. It can serve as a model for other world regions to adapt.